2010
DOI: 10.1097/brs.0b013e3182023796
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fusion in Octogenarians

Abstract: Surgical treatment need not be withheld on the basis of age; elderly patients can successfully be treated using MIS techniques, and are-in our experience-among the most satisfied with their outcomes, enjoying significant improvements in pain, mobility, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…At least two studies reported change in hemoglobin, presumably independently measured, but did not separately report patient fluid balance [12,13] . No studies used defined criteria for or an independent or blinded observer to decide the following study parameters: (1) Hospital discharge eligibility (i.e., LOS); (2) Opiate prescription or availability; and (3) Need for perioperative transfusion.…”
Section: Overall Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At least two studies reported change in hemoglobin, presumably independently measured, but did not separately report patient fluid balance [12,13] . No studies used defined criteria for or an independent or blinded observer to decide the following study parameters: (1) Hospital discharge eligibility (i.e., LOS); (2) Opiate prescription or availability; and (3) Need for perioperative transfusion.…”
Section: Overall Resultsmentioning
confidence: 99%
“…Identified pertinent studies are shown in Table 1, including three randomized controlled trials (RCTs) (Cho et al [14] , Usman et al [15] and Watanabe et al [16] ), one incompletely randomized trial (Mobbs et al [17] ; randomized by consecutive, odd/even patient order [18] ), and one cohort comparison study [12] . In Table 2 Three studies specifically examined rates of post operative pain in these patient groups.…”
Section: Laminectomymentioning
confidence: 99%
See 3 more Smart Citations